PERAN KOMUNIKASI ASERTIF TERHADAP RESOLUSI KONFLIK SISWA DI KELAS - Firdaus Christina Nathasya; Evi Winingsih; Budi Purwoko (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
Conflicts that occur in classroom settings often arise from differences in perception, unclear task distribution, and a lack of open communication. These situations can disrupt learning processes and social relationships among students if not properly addressed. This study aims to analyze the role of assertive communication in classroom conflict resolution. A descriptive qualitative approach with a case study design was employed, involving five students selected through purposive sampling. Data were collected through semi-structured interviews, open-ended questionnaires, and classroom observations, and were analyzed using the thematic analysis model of Miles, Huberman, and Saldaña. The findings indicate that assertive communication plays a crucial role in three main aspects of conflict resolution: clarifying misunderstandings, facilitating informal peer mediation, and preventing conflict escalation by fostering an open and respectful communication climate. Students who demonstrated assertive communication tended to resolve conflicts constructively and acted as natural mediators in the classroom. These findings highlight the importance of developing assertive communication skills as part of instructional strategies and character education.